2017
DOI: 10.1111/imr.12559
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role for CD69 in allergic inflammatory responses: CD69‐Myl9 system in the pathogenesis of airway inflammation

Abstract: CD69 has been known as an early activation marker of lymphocytes; whereas, recent studies demonstrate that CD69 also has critical functions in immune responses. Early studies using human samples revealed the involvement of CD69 in various inflammatory diseases including asthma. Moreover, murine disease models using Cd69 mice and/or anti-CD69 antibody (Ab) treatment have revealed crucial roles for CD69 in inflammatory responses. However, it had not been clear how the CD69 molecule contributes to the pathogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 144 publications
0
57
0
Order By: Relevance
“…We recently identified myosin light chain (Myl) 9 and Myl12 as functional ligands for CD69 (45). We also showed that the interaction between CD69 on Th2 cells and Myl9 expressed on the luminal side of endothelial cells in the blood vessels recruits activated Th2 cells to the inflammatory site, resulting in airway inflammation (45, 46). CD69 on iNKT cells might therefore induce the migration of iNKT cells to the lung by binding to Myl9 or Myl12 and also play a critical role in the development of AHR and airway inflammation (Figure 1).…”
Section: Lung Inkt Cell-dependent Allergic or Non-allergic Asthmamentioning
confidence: 78%
“…We recently identified myosin light chain (Myl) 9 and Myl12 as functional ligands for CD69 (45). We also showed that the interaction between CD69 on Th2 cells and Myl9 expressed on the luminal side of endothelial cells in the blood vessels recruits activated Th2 cells to the inflammatory site, resulting in airway inflammation (45, 46). CD69 on iNKT cells might therefore induce the migration of iNKT cells to the lung by binding to Myl9 or Myl12 and also play a critical role in the development of AHR and airway inflammation (Figure 1).…”
Section: Lung Inkt Cell-dependent Allergic or Non-allergic Asthmamentioning
confidence: 78%
“…Furthermore, FACS analysis showed increased CD69 expression on B7‐H3Bi‐Ab‐ATC over their unarmed ATC counterpart after 18‐hour incubation with T24 and T24/DDP cells (Figure B). CD69 has been known as an early activation marker of lymphocytes and has critical functions in immune responses . Increased CD69 expression on B7‐H3Bi‐Ab‐ATC proved that ATC was activated by B7‐H3Bi‐Ab.…”
Section: Resultsmentioning
confidence: 99%
“…CD69 has been known as an early activation marker of lymphocytes and has critical functions in immune responses. 33 Increased CD69 expression on B7-H3Bi-Ab-ATC proved that ATC was activated by B7-H3Bi-Ab. We used the same experiment in unactivated PBMCs.…”
Section: Cytotoxicity Effects Of B7-h3bi-abarmed Atc On Bladder Canmentioning
confidence: 97%
“…Th2 or Th17 cells infiltrate into the small vessels of the inflamed lung, re‐express CD 69 and interact with the CD 69 ligand Myl9, which is located at the luminal surface of small vessels and forms net structures (Myl9 net) in the vessels in inflamed lungs. Such CD 69‐Myl9 interaction may help the infiltration of antigen‐specific Th2 cells into the inflamed lung . Upon antigen stimulation, the infiltrated Th2 cells produce IL ‐4, IL ‐5, and IL ‐13 to induce eosinophilic inflammation, mucus hyper production and airway hyperreactivity.…”
mentioning
confidence: 99%
“…Such CD69-Myl9 interaction may help the infiltration of antigen-specific Th2 cells into the inflamed lung. 29,30 Upon antigen stimulation, the infiltrated Th2 cells produce IL-4, IL-5, and IL-13 to induce eosinophilic inflammation, mucus hyper production and airway hyperreactivity. Th17 cells induce neutrophilic inflammation, which is steroid-resistant.…”
mentioning
confidence: 99%